RETRACTED: MiR-519b-3p Inhibits the Proliferation and Invasion in Colorectal Cancer via Modulating the uMtCK/Wnt Signaling Pathway - Zhang, Yuexiang; Sun, Miao; Chen, Yusha; Li, Bixun (Frontiers in Pharmacology, 2019)
Dysregulation of microRNAs (miRNAs) as well as their targeted downstream genes have been suggested to be involved in the carcinogenesis and progression of colorectal cancer (CRC). Our study detected the expression of miR-519b-3p in CRC patients, and determined the potential role of miR-519b-3p in the migration and invasion in CRC. The impact of abnormal expression of miR-519b-3p on the proliferation and invasion of CRC cells were explored. Rescue detections were performed to explore the impact of miR-519b-3p on biological behaviors of CRC cells. We indicated here that miR-519b-3p was notably reduced in CRC specimen and the CRC cell lines. The luciferase assay identified that in CRC, 3'-UTR of ubiquitous mitochondrial creatine kinase (uMtCK) was the direct targeted binding site of miR-519b-3p. Furthermore, the overexpression of miR-519b-3p inhibited the proliferation and invasion of RKO and DLD-1 CRC cell lines. Whereas miR-519b-3p-knockdown was demonstrated to exert contrary effect. Additionally, miR-519b-3p expression was negatively correlated with uMtCK mRNA in CRC specimens. Notably, the overexpression of miR-519b-3p suppressed the uMtCK/Wnt signaling pathway in CRC cells. Mechanically, restoration of uMtCK expression remarkably diminished the anticancer effect of miR-519b-3p in colon cancer cells. What we found here indicated that miR-519b-3p inhibited CRC cell proliferation and invasion via suppressing uMtCK expression. The inhibition of uMtCK by miR-519b-3p may provide a promising treatment option for CRC.